Classification of natural and engineered rock slopes using UAV photogrammetry for assessing stability. Issue 1 (August 2021) - Bar, N; Borgatti, L; Donati, D; Francioni, M; Salvini, R; Ghirotti, M
Abstract: Ground failure on natural and engineered rock slopes is a geological hazard with potentially fatal consequences to the public or personnel in the mining industry. Aerial reconnaissance with the use of unmanned aerial vehicles (UAV) is rapidly becoming standard practice for geotechnical and engineering geological site investigations, enabling faster and safer data collection on slopes, which are often difficult to access on foot. Data obtained from aerial reconnaissance alongside conventional field investigations assist in the development of an engineering geological model that can form the basis of various stability analyses including kinematic, limit equilibrium and finite element analyses, and even rock fall simulations. This paper presents two case studies in which remote reconnaissance is used as an initial method of site investigation to classify natural and engineered rock slopes. The case studies from San Leo in Italy and an open pit mine in the Caribbean are used to demonstrate the effectiveness of these techniques for developing a preliminary engineering geological model from which stability analyses can be derived to predict future ground behaviour to assist in managing risks associated with the geological hazard.